Improving Nursing Night Shifts: The Importance of Low Light and Proper Breaks (Global Journal of Management and Business Research, 2025)
Abstract not found
Keywords: nurses; working conditions; night shifts; circadian rhythm; melatonin; cortisol; ambient lighting; rest breaks; sleep deprivation